Effect of Personal Intelligence and Organizational Culture on Employee Performance of SMEs Fashion Industry In Bandung - Imas Soemaryani; Hilmiana Hilmiana; Sipa Paujiah (Jurnal Bisnis Manajemen, 2016)
The manufacturing sector in the city of Bandung contributes approximately 25.45% in 2013 but the contribution decreases by 24.29% in 2014 and 2015. This is caused by the decrease in employee performance of SMEs in this sector as a result of the low personal intelligence and organizational culture. This research studied 10 SMEs (medium scale) of Muslim fashion industry in Bandung, registered in BPPKU Kadin (chamber of commerce) Bandung. This study is aimed at determining the effect of personal intelligence and organizational culture on employee performance of SMEs either partially or simultaneously. The method used is explanatory research. The results showed that personal intelligence and organizational culture significantly influence employee performance of medium scale SMEs of Muslim fashion industry in Bandung either partially or simultaneously.